Biblical Greek illustrated by examples - Zerwick, Maximilian, 1901-1975; Smith, Joseph (Rome, Italy Editrice Pontificio Istituto Biblico, 1990)
Includes bibliographical references.
Donated by Engadine Bible Centre
Keywords: Greek language, Biblical -- grammar